If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + -9n = 2 Solving 3m + -9n = 2 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '9n' to each side of the equation. 3m + -9n + 9n = 2 + 9n Combine like terms: -9n + 9n = 0 3m + 0 = 2 + 9n 3m = 2 + 9n Divide each side by '3'. m = 0.6666666667 + 3n Simplifying m = 0.6666666667 + 3n
| 2g-5=6 | | 2z-3=4z-1 | | 6a^2+12a-48=0 | | 36=3x+2+6x+7 | | (2x+5)8=72 | | -36-52= | | 4.5-1.5(6m+2)=3 | | 7+3*4-1=39 | | 3y-4(y+2)=2(3y-2) | | -1-10(10r+6)= | | -3n-5n=8 | | 5x^2+5y=45 | | 3z-9=3 | | -2x+6=16 | | 7p=35 | | (x-5)(x-6)=6 | | 4x-7=7x-5 | | x^4-17x^2+52=0 | | 3a-15=-6 | | 3y/2=-6 | | 4x+20=53-2x | | y=7x^2-x+11 | | V^2-2v=4v+40 | | 17=(3x) | | 5x/6=30 | | 0.2x=10 | | 6x-18+4y-20=170 | | 8b+3-10b=2(b-2)+3 | | -3x+-7=-22 | | 2x-2-12=3x-3 | | 6gh-15h+10-4g= | | 12x-4=13x-5 |